Constraints on the dark matter from the relative motion of the galaxies - L. Khokhlov, Dr. (International Journal of Advanced Astronomy, 2022)
The method is considered of deriving the dynamical masses of the neighbouring galaxies from their relative motion. The method allows to constrain the dark matter in galaxies, independently of the model of dark matter. The following pairs of galaxies were studied, the Milky Way and M31, Cen A and M83 as well as the brightest galaxies in the Virgo cluster, M87 and M60, M87 and M89, M87 and M49. The dynamical masses of the galaxies obtained from the relative motion of the galaxies are smaller than the total masses of the galaxies obtained in the Î›CDM model.Â Â Â